Fabrication and its characterisation of zirconia and alumina reinforced experimental nanohybrid dental luting composite using silica from rice husk - Islam , Md Saiful; Raja Awang, Raja Azman; Jamayet, Nafij; Ismail, Noor Huda (Bangladesh Journal of Medical Science, 2025)
Objectives Silanisation of dental filler strengthens the bonding within the resin matrix. This study aims to characterise silanated silica, zirconia, and alumina fillers, then nanohybrid dental luting composite cement (NHC) using the fillers. Materials and Methods Charaterisation of unsilanated and silanated silica, zirconia and alumina fillers was performed using FTIR and FESEM for microstructure analysis. Five NHC groups: silica only; 3 wt% zirconia; 3 wt% alumina; 3 wt% zirconia and 2 wt% alumina; and Rely-XTM U200. Results and Discussion From the FESEM analysis, the silanated fillers were homogeneously dispersed in NHC. Conclusion NHC made of silica rice husk with reinforcement of zirconia and alumina has potential in the market. BJMS, Vol. 24 No. 03 July’25 Page : 866-872